2011
DOI: 10.1093/cvr/cvr257
|View full text |Cite
|
Sign up to set email alerts
|

The natural cardioprotective particle HDL modulates connexin43 gap junction channels

Abstract: Short-term treatment with HDL or S1P induces phosphorylation of Cx43 by a PKC-dependent pathway. HDL-induced phosphorylation of Cx43 reduced the diffusion of large tracer molecules between cells, whereas impulse conduction was maintained. Moreover, 5 min treatment with HDL confers cardioprotection against ischaemia/reperfusion injury. These results link Cx43 for the first time to the short-term cardioprotective effects of HDL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 29 publications
2
23
0
3
Order By: Relevance
“…In agreement with this prior study, rHDL improved cardiac function (Rossoni et al 2004) and reduced infarct size compared to non-treated animals (Gu et al 2007). Recent studies showed that treatment with HDL significantly reduced the infarct size in rodents submitted to IRI compared to non-treated IRI animals (Frias et al 2013;Morel et al 2012). The protective impact of HDL or rHDL did not depend on the timing of injection.…”
Section: Iri In the Isolated Heart Modelmentioning
confidence: 90%
See 2 more Smart Citations
“…In agreement with this prior study, rHDL improved cardiac function (Rossoni et al 2004) and reduced infarct size compared to non-treated animals (Gu et al 2007). Recent studies showed that treatment with HDL significantly reduced the infarct size in rodents submitted to IRI compared to non-treated IRI animals (Frias et al 2013;Morel et al 2012). The protective impact of HDL or rHDL did not depend on the timing of injection.…”
Section: Iri In the Isolated Heart Modelmentioning
confidence: 90%
“…These studies suggest that the cardioprotective effect involves the activation of the pro-survival proteins ERK1/2 and STAT3, but not p38 MAPK. HDL also induces the phosphorylation of connexin 43 (Morel et al 2012). This phosphorylation leads to a reduction in gap junction permeability, which may limit the spread of mediators implicated in death pathways.…”
Section: Effects Of Hdl In Rat Neonatal Cardiomyocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many pharmacological interventions which reduce infarct size after ischemia/reperfusion such as blockade of p38 MAPK (Surinkaew et al, 2013), high density lipoprotein/sphingosine-1 phosphate (Morel et al, 2012), PKC epsilon activating peptide (Lancaster et al, 2011), FGF2/diazoxide (Srisakuldee et al, 2009) or estradiol (Lee et al, 2004) preserved Cx43 phosphorylation during ischemia/reperfusion, although causality between altered Cx43 phosphorylation and reduced infarct size was proven only in one study (Srisakuldee et al, 2009). …”
Section: Myocardial Ischemia/reperfusion Injury and Cardioprotectionmentioning
confidence: 99%
“…S1P improves cardiomyocyte survival during hypoxia [ 122 ], protects against doxorubicin toxicity [ 123 ], promotes phosphorylation of connexin 43 [ 124 ] and activates Stat3, a transcription factor with an important role in adaptation of myocardium to stress [ 125 , 126 ].…”
Section: Ischemiamentioning
confidence: 99%